Optimalisasi Fungsi Legislasi Badan Musyawarah Kampung - Silambi, Erni Dwita; Samderubun, Fransiskus; Ruslan, Achmad; Halim, Hamzah (SASI, 2021)
This study aims to optimize the implementation of the legislative function in the village consultative organization. This study using sociolegal law research methods, data collection techniques used are interviews, direct observation, literature study. All data obtained from this study, both primary data, secondary data, and tertiary data, are then processed and analyzed qualitatively for further description in order to provide understanding by explaining the results of this study, ideally, it discusses and agrees on a village regulation draft from the right of initiative. The proposal purpose is to gather the aspirations from the village community and stipulated in a village regulation product. However, the implementation of proposals and designs proposed by the Village Deliberative Council was low, resulting in the lack of village regulations being produced. There are 179 villages in Merauke district, none of it has village regulation product initiatively.. The decline performance of the Village Deliberative Council will result in ineffective legislative functions. Appropriate regulations, namely renewal and improvement in terms of Quality, Quantity, Timeliness, Effectiveness, Independence, Environment, become benchmarks in optimizing the legislative function of Village Deliberative Council. Something questionable here is whether the village community can follow the changes or reject the changes.